Predominant Bacterial Diversity in Rheumatoid Arthritis Rat After Treated with Caprine CSN1S2 Protein - Eko Suyanto; Fatchiyah Fatchiyah (Journal of Tropical Life Science, 2021)
Introduction: Rheumatoid arthritis (RA) is an autoimmune and systemic inflammatory disease influenced by microbial abnormalities (dysbiosis) in the intestinal that affect changes in metabolism and immune system disorders. This study aimed to investigate the predominant intestinal microbiota in complete Freund’s Adjuvant-induced rheumatoid arthritis rats after treated with caprine milk CSN1S2 protein through fecal analysis based on PCR-DGGE and to construct the phylogenetic tree of bacteria as the evolutionary relationship. Method: The experimental animals were divided into 6 groups with 2 types of rat model, namely control rat (C group, CM group, and CY group) and RA rat (RA group, RAM group, and RAY group). Predominant cultivable microbiota was obtained by direct culture and analyzed using PCR-DGGE with some specific primers. The DNA sequences were analyzed and aligned using bioinformatics software to construct the phylogenetic tree. Results: We found that Lactobacillus group significantly increased in the control rat model and the predominant intestinal bacteria in RA rats were Enterococcus group (Enterococcus faecium and Enterococcus faecalis). Conclusions: The caprine milk CSN1S2 protein influences the composition of microbiota in RA rats with the emergence of predominant bacteria that are considered species of the Bacillus group, closely related to Bacillus coagulans, which can be promoted the growth of B. coagulans to suppress pathogenic bacteria in the development of RA disease.